Enhancing EFL Speaking Skills of Secondary School Students through a Constructivist Learning Activities (CLAs) Program - Emad Shalaby; Salah Badr (Port Said Journal of Educational Research, 2024)
The present study aimed to examine whether a suggested program based on constructivist learning activities (CLAs) has any impact on the development of English-speaking skills among secondary school EFL students. The CLAs were implemented in a collaborative learning environment, where learners were encouraged to work together to complete tasks and solve problems. To achieve this objective, a one-group pretest-posttest quasi-experimental design was employed. A single intact class of 30 students served as the sole participant group. To assess learners' speaking proficiency, a pre-post speaking test was developed and administered before and after the program's implementation. A paired-sample t-test was used to analyze the data statistically, and the effect size was calculated using Eta Squared h2. Results showed a positive effect of the suggested program on enhancing English-speaking skills among secondary school EFL students. The findings of the current study have important implications for EFL teachers. They suggest that teachers should use CLAs to develop learners’ speaking skills. CLAs provide learners with chances to practice speaking in a wide range of contexts and to receive feedback from their peers and teachers. This can be beneficial for learners to develop their speaking fluency, pronunciation, vocabulary, and grammar.